Cold Exposure After Exercise Impedes the Neuroprotective Effects of Exercise on Thermoregulation and UCP4 Expression in an MPTP-Induced Parkinsonian Mouse Model - Tsai, Yi-Ju; Jhong, Yue-Cih; Ching, Shih-Hong; Liao, Yu-Ching; Ching, Cheng-Hsin; Chuang, Jih-Ing (Frontiers in Neuroscience, 2020)
Moderate exercise and mild hypothermia have protective effects against brain injury and neurodegeneration. Running in a cold environment alters exercise-induced hyperthermia and outcomes; however, evaluations of post-exercise cold exposure related to exercise benefits for the brain are relatively rare. We investigated the effects of 4C cold exposure after exercise on exercise-induced thermal responses and neuroprotection in an MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-induced Parkinsonian mouse model. Male C57BL/6J mice were pre-treated with MPTP for 5 consecutive days and follow-up treadmill exercise for 4 weeks. After 1-h running at a 22C temperature, the mice were exposed to a 4C environment for 2 hours. An MPTP injection induced a transient drop in body and brain temperatures while mild brain hypothermia was found to last for 4 weeks after MPTP treatment. Preventing brain hypothermia by exercise or 4C exposure was associated with an improvement in MPTP-induced striatal uncoupling protein 4 (UCP4) downregulation and nigrostriatal dopaminergic neurodegeneration. However, 4C exposure after exercise abrogated the exercise-induced beneficial effects and thermal responses in MPTP-treated mice, including a low amplitude of exercise-induced brain hyperthermia and body temperature while at rest after exercise. Our findings elucidate that post-exercise thermoregulation and UCP4 expression are important in the neuroprotective effects of exercise against MPTP toxicity.